A new conceptual design approach for overcoming the flaws of functional decomposition and morphology. Issue 7 (2nd July 2016) - Fiorineschi, Lorenzo; Rotini, Federico; Rissone, Paolo
ABSTRACT: Some scholars have recently criticised functional decomposition and morphology (FDM) approaches despite their wide diffusion in academia. More precisely, several research projects demonstrated that such methods suffer from poor diffusion in industry because of some deficiencies. This paper, which focuses on evidence that is addressed by the literature, refers to a new conceptual design approach that can overcome the flaws of FDM. More specifically, this paper presents the fundamental logic and the main tools that constitute the groundings of the proposal. Analogies and differences with respect to the classical methodology are examined by means of a literature case study, while two academic studies are briefly introduced to show other peculiarities of the suggested proposal. The same case study applications are later used to highlight the current shortcomings of the new approach and to formulate possible future developments.